HUBUNGAN PELATIHAN, STATUS KERJA, LATAR BELAKANG PENDIDIKAN, DAN PENGGUNAAN ALAT PELINDUNG DIRI DENGAN TERJADINYA KECELAKAAN KERJA PADA TOTAL E&P INDONESIE - Lambang Aryanto; Ekawati Ekawati; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2016)
Well connection activity was a very important stage in oil and gas company, finishing well connection activity would influence the improvement of oil and gas production. The process of well connection demanded the workers to work carefully, fastly, and highly strength Well connection activity requires workers to work carefully, fastly, and with highly strength with the result that the threat of workplace accident became a very high risk to the workers. The purpose of this study was to determine the relationship between training, employment status, educational background, and the use of personal protective equipment with workplace accident in the process of installation platform of well connection project on Tunu field of block Mahakam TOTAL E & P INDONESIE. The method of this research was quantitative explanatory research with cross sectional approach. The subject of this research was the platform installation workers of well connection project unit construction engineering, which amounted to 42 respondents. This research was located in Tunu of Mahakam Block, TOTAL E & P INDONESIE. The Source of primary data were obtained through questionnaires and observation. The data analysis was using chi square test. The results showed that there were 14,3% workers with permanent employment status, 73,8% workers with a good training, 64,3% workers with a good background, 50,0% workers with the use of personal protective equipment properly, and 45,2% workers ever had an accident of 42 respondents. While the bivariate analysis showed that there was no relationship between employment status and workplace accident (p value = 1.000) there was no relationship between educational background and workplace accident (p value = 0.055). However, there was a relationship between training and workplace accident (p value =0,000) , there was a relationship between the use of personal protective equipment with workplace accident (p value = 0,012). It was recommended in training to give a pre-test and a post-test to measure the effectiveness of training.